The Role of Kiai in Forming Santri Independence : Qualitative Study at Al-Ittifaq Islamic Boarding School Ciwidey Bandung, West Java - Ahyar Ahmad Sirojudin; Achmad Sanusi; Abin Syamsudin M; Nanang Hanafiah (Journal of Islamicate Studies, 2020)
The title of this research is "Management of Islamic Boarding School Education in Establishing the Independence of Santriâ€ (qualitative case study at Al-Ittifaq Islamic Boarding School Ciwidey-Bandung, West Java). This topic is raised because the management of Islamic Boarding School (pesantren) education in shaping the independence of the students (Santri) is highly needed. Santri at the Islamic Boarding Schools are given knowledge, values and life skills. Armed with expertise, when students are in the communit they will not get a difficulty in getting a job. The purpose of this research is to observe and study how the real activities at Al-Ittifaq Islamic Boarding School Ciwidey-Bandung, on attitudes, skills and independence. Kiyai has a major role in the success of this matter, because Kiai has a strong Islamic character, which is reflected in thoughts, actions and words, which become learning for students both directly and indirectly. With Islamic boarding school education management, students (Santri) can determine business opportunities and be given knowledge of the methods developed by the Prophet Muhammad. The value of honesty through reliable and objective words has an impact on the attitudes and behavior of the students to be honest, not manipulative, especially in entrepreneurship.